2020
DOI: 10.3389/fmolb.2019.00149
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Uses Mce Proteins to Interfere With Host Cell Signaling

Abstract: Tuberculosis continues to be the main cause for mortality by an infectious agent, making Mycobacterium tuberculosis one of the most successful pathogens to survive for long durations within human cells. In order to survive against host defenses, M. tuberculosis modulates host cell signaling. It employs many proteins to achieve this and the Mce proteins are emerging as one group that play a role in host cell signaling in addition to their primary role as lipid/sterol transporters. Mce proteins belong to the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…The genomes of isolates 335427 T and 234509 T contained 167 and 154 genes, respectively, encoding for virulence factor proteins, including those involved in adherence to the host cells ( Figure 2 ). In this context, the mce proteins which were found on the mycobacterial cell surface and found to play a role in invading the host cell during infection were also detected in Nocardia species [ 72 ]. Isolate 335427 T presented the complete mce operons 5, 7 and 9, while isolate 234509 T had operons 7 and 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomes of isolates 335427 T and 234509 T contained 167 and 154 genes, respectively, encoding for virulence factor proteins, including those involved in adherence to the host cells ( Figure 2 ). In this context, the mce proteins which were found on the mycobacterial cell surface and found to play a role in invading the host cell during infection were also detected in Nocardia species [ 72 ]. Isolate 335427 T presented the complete mce operons 5, 7 and 9, while isolate 234509 T had operons 7 and 6.…”
Section: Resultsmentioning
confidence: 99%
“…Isolate 335427 T presented the complete mce operons 5, 7 and 9, while isolate 234509 T had operons 7 and 6. All the operons showed identical genes: two inner membrane permeases YrbEa and YrbEb and six mceA-F integral membrane proteins [ 72 , 73 ]. In contrast, the closest phylogenetic species N. asiatica NBRC 100129 T was devoid of any mce operon on its draft genome sequence unlike N. abscessus NBRC 100374 T which had operons 5, 6 and 7.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins encoded by mce genes have been described to interfere with host cell signaling and it has been shown that mutation of these genes affects M . tuberculosis virulence in mice [ 36 , 37 ]. Also, the expression of two metabolic genes and their regulator namely prpD , prpC and prpR (enoding methylcitrate dehydratase, methylcitrate synthase and their transcriptional regulator, respectively; Fig 4C ) were decreased in AF2122:: pknH TB relative to WT.…”
Section: Resultsmentioning
confidence: 99%
“…Four closely related ATP-binding cassette (ABC) transporter-like complexes called Mce are responsible for the import ( Wilburn et al, 2018 ). Three of the Mce proteins represent Lpp ( Fenn et al, 2019 ). Mce proteins are involved in modulating host cell signaling and allow the growth with cholesterol as sole C-source.…”
Section: Function Of Lpp In Gram+ Bacteriamentioning
confidence: 99%